2017
DOI: 10.1038/nnano.2017.124
|View full text |Cite
|
Sign up to set email alerts
|

Photo-excited hot carrier dynamics in hydrogenated amorphous silicon imaged by 4D electron microscopy

Abstract: Charge carrier dynamics in amorphous semiconductors has been a topic of intense research that has been propelled by modern applications in thin-film solar cells, transistors and optical sensors. Charge transport in these materials differs fundamentally from that in crystalline semiconductors owing to the lack of long-range order and high defect density. Despite the existence of well-established experimental techniques such as photoconductivity time-of-flight and ultrafast optical measurements, many aspects of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 29 publications
4
51
3
Order By: Relevance
“…The spatial and temporal dynamics of charged particles at the interfaces of materials is of vital consequence to several modern technologies, such as light-harvesting and semiconductor devices. For example, the mobility of carriers ( 1 ) and the underlying nature of diffusion ( 2 ) raise important questions relevant to semiconductor device technology. In the case of photocatalysis, where light energy is converted to chemical energy at the surface of a semiconductor, spatiotemporal dynamics of the photocarriers directly affects surface chemical reactions ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial and temporal dynamics of charged particles at the interfaces of materials is of vital consequence to several modern technologies, such as light-harvesting and semiconductor devices. For example, the mobility of carriers ( 1 ) and the underlying nature of diffusion ( 2 ) raise important questions relevant to semiconductor device technology. In the case of photocatalysis, where light energy is converted to chemical energy at the surface of a semiconductor, spatiotemporal dynamics of the photocarriers directly affects surface chemical reactions ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…SUEM experiences the same charging issue as the normal SEM, so in principle is not suitable to study electrically insulating materials, although the environmentalmode SUEM [29] can be a potential solution. SUEM has been utilized to image ultrafast photocarrier dynamics on the surface of a wide range of materials, including crystalline semiconductors [28,30], semiconducting nanowires [31] and nanocrystals [32], amorphous semiconductors [33], semiconductor p-n junctions [34] and two-dimensional materials [35], and these applications have resulted in intriguing observations such as ballistic transport of photocarriers across a p-n junction [34], superdiffusion of photocarriers in heavily-doped semiconductors [30] and spontaneous spatial separation of electrons and holes in amorphous semiconductors [33]. Whereas there has been an abundance of recent reviews of ultrafast electron microscopy [8,9,[36][37][38], we dedicate this article specifically to SUEM, with an emphasis on the current understanding of various physical processes that contribute to the contrast images observed in SUEM from a users' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Both thermal and carrier effects induced by optical excitation can modify the refractive index. [ 54 ] We observe the reflection decay in Figure 3C,D is much slower than the typical carrier decay (1 ns) [ 55 ] but follows well the predicted temperature transient. Studies indicated the inverted position of the isentropic band gaps from c‐Si and a‐Si lead to positive and negative temperature coefficients (d n /d T ) [ 56 ] in 633 nm.…”
Section: Resultsmentioning
confidence: 57%